Implementasi Sistem Informasi Akuntansi Berbasis Website pada Sekolah Insan Teladan Pekanbaru - Bidiana; Satria Perdana Arifin (Politeknik Caltex Riau, 2021)
Pekanbaru Teladan Insan School is an educational institution engaged in the service sector. In managing and recording the school finances, the treasurer makes use of spreadsheets and books in recording transactions that are classified as simple. The results of interviews with the school treasurer, financial records are still made manually and in finding the required transaction history data, the treasurer needs to look for the financial reports that have been archived, as a result the financial reports to be submitted to the head of the Foundation need to be corrected because there are errors in the calculations and the time for submitting financial statements takes 1-3 working days. The solution to the existing problems is to build an accounting information system that replaces the manual process. The “Website-Based Accounting Information System” for the Pekanbaru School of Exemplary People is designed to assist the school treasurer in handling the recording of routine transactions which include income, school expenses, and others. The results of transactions carried out by the treasurer will be directly evaluated by the head of the Foundation through the system. Based on the tests that have been done using the Test Case from Black Box Testing, the results are 100% by testing 44 items. The results of the test of accounting experts, namely PCR lecturer Fifitri Ali, S.S.T., M.Sc, that the system has met accounting standards in the service sector